The effect of anaerobic remineralization of the seagrass Halophila stipulacea on porewater biogeochemistry in the Gulf of Aqaba - Soto, Neta; Winters, Gidon; Antler, Gilad (Frontiers in Marine Science, 2023)
Introduction Seagrasses form oxidizing microenvironments around their roots, creating complex and strong redox gradients, thus affecting the rates of microbial carbon mineralization in their surrounding sediments. Since seagrasses are continuously being lost worldwide, a deeper understanding of the changes that occur within different seagrass sediments following the disappearance of the plants is of ecological and global importance. Methods We conducted a slurry experiment with sediments that have different characteristics from the northern tip of Gulf of Aqaba; the different sediments included different compartments of the tropical seagrass Halophila stipulacea (old and young leaves, rhizomes, or roots). We measured the changes over time in dissolved inorganic carbon (DIC), alkalinity, ferrous iron (Fe2+), hydrogen sulfide (H2S), sulfate (SO42-), and sulphur isotope ratios in sulfate within water. These measurements were used to calculate the rate of remineralization of each seagrass compartment, allowing us to predict the potential effects of the disappearance of different H. stipulacea compartments on key microbial processes in the surrounding environment. Results We show that H. stipulacea’s rhizomes had the fastest decomposition rates, followed by the young leaves, roots, and old leaves (which also indicates the preservation potential of old leaves). Discussion High concentrations of hydrogen sulfide were detected only in the slurries containing rhizomes and young leaves. High sulfide concentrations can lead to seagrass mortality and cause a positive feedback loop where the loss of seagrass due to sulfide generates further sulfide accumulation. This positive feedback loop can also be further reinforced by the loss of burrowing fauna in the sediment. This emphasizes the importance of understanding the extent of different pathways of seagrass disappearance on the surrounding environment and other geochemical feedbacks.